Everyday Language Exposure Shapes Prediction of Specific Words in Listening Comprehension: A Visual World Eye-Tracking Study - Ito, Aine; Sakai, Hiromu (Frontiers in Psychology, 2021)
We investigated effects of everyday language exposure on prediction of orthographic and phonological forms of a highly predictable word during listening comprehension. Native Japanese speakers in Tokyo (Experiment 1) and Berlin (Experiment 2) listened to sentences that contained a predictable word and viewed four objects. The critical object represented the target word (e.g., 魚 /sakana/; fish), a word that was orthographically similar (e.g., 角 /tuno/; horn) or phonologically similar (e.g., 桜 /sakura/; cherry blossom) to the target word, or an unrelated word (e.g., 本 /hon/; book). The three other objects were distractors. The Tokyo group fixated the target and orthographic competitor objects over the unrelated objects before the target word was mentioned, suggesting that they pre-activated orthographic form of the target word. In contrast, the Berlin group showed a weaker bias towards the target than the Tokyo group, and they showed a tendency to fixate the orthographic competitor only when the orthographic similarity was very high. These findings suggest a link between everyday language exposure and prediction. We found no evidence for prediction of phonological information. The obtained group differences support probabilistic models of prediction, which regard the built-up language experience as a basis of prediction.